Revisiting Pattern of Democratic Transition in Indonesia and Turkey - Muhammad Sya'roni Rofi'i (Jurnal Transformasi Global, 2016)
The democratic transition is one of the most decisive phases for the sustainability of democracy in every country. The success of a country in managing its democratic transition after the fall of military regime has significant impact on the effort to establish constitutional liberal democratic country, where civil supremacy over military established, civil liberties guaranteed, role of civil society increased and check and balances mechanism growth. Indonesia and Turkey are two countries that emerged as key player in their region and could become models for democratic transition in their own region respectively. Holding the predicate as majority Muslim country with secular character gives them privilege to claim the status as model for democracy in the Muslim World and in the Middle East as whole. In the post Arab Spring where some countries attempt to find model for their transition, the experience of both countries are considerable. This paper discusses the experiences of Indonesia and Turkey in managing democratic transition and the direction of democracy in both countries. Keywords: democratic transition, civil-military relation, Indonesia, Turkey